2020
DOI: 10.1038/s41467-020-16306-5
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine regulates glycolysis of cancer cells through PDK4

Abstract: Studies on biological functions of N 6-methyladenosine (m 6 A) modification in mRNA have sprung up in recent years. We find m 6 A can positively regulate the glycolysis of cancer cells. Specifically, m 6 A-sequencing and functional studies confirm that pyruvate dehydrogenase kinase 4 (PDK4) is involved in m 6 A regulated glycolysis and ATP generation. The m 6 A modified 5′UTR of PDK4 positively regulates its translation elongation and mRNA stability via binding with YTHDF1/eEF-2 complex and IGF2BP3, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
194
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(221 citation statements)
references
References 58 publications
6
194
2
Order By: Relevance
“…m6A plays critical roles in tumorigenesis and tumor progression [37] , [38] , [39] . Studies showed m6A can regulate the maturation and the ability of neoantigens presentation in immune cells, and regulate response to immunotherapy [ 5 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…m6A plays critical roles in tumorigenesis and tumor progression [37] , [38] , [39] . Studies showed m6A can regulate the maturation and the ability of neoantigens presentation in immune cells, and regulate response to immunotherapy [ 5 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 m6A modification can influence mRNA decay, splicing, transport, localization, and translation. 15,16 In mammalian cells, m6A modification is dynamic, reversible, and catalyzed by m6A methyltransferases (METTL3, METTL14, and WTAP), also known as "writers". m6A demethylases (FTO and ALKBH5), also known as "erasers", are responsible for directly removing m6A modification of mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, METTL3 was involved in m 6 A-regulated glycolysis, which was one of the critical hallmarks of tumor growth. METTL3 enhanced the stability of pyruvate dehydrogenase kinase 4 (PDK4) and HK2 mRNAs in a METTL3-m 6 A-YTHDF1-dependent manner, ultimately promoting tumor growth and chemoresistance [ 116 ].…”
Section: Mettl3 Mediates Tumorigenesis Via Rna Methylationmentioning
confidence: 99%